Training Installation and Configuration Network Computer Simple for Students of Cipta Insani Vocational School Independent - Rino Subekti; Devi Puspitasari; Ghanistantiono Ghanistantiono; Dade Maulana; Erdiek Ardhianto; Muhammad Raihan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Training installation and configuration network computer simple for students of Cipta Insani Vocational School Independent aiming For increase understanding and skills student in build as well as manage network computer . The method used in devotion This is approach practical through session theory and practice directly , where students given material about the basics network , device hard used , as well as steps installation and configuration . The results of training This show improvement knowledge student about network computer , which is measured through pre-test and post-test, as well bait come back positive from participant about involvement and implementation material . With training this , it is expected student can implement knowledge gained​ in projects at school and in the world of work in the future . The success of this program shown with activity all participants and enthusiasts participant do discussion and results questionnaire satisfaction show by 90.50% of participants satisfied with existence training This Because can increase understanding as well as ability practical student about Network Computer